Results of anthropological examination of the case of Klippel-Feil syndrome with palatoschisis - Henneberg, Maciej; OtockiOtocki, Piotr (Anthropological Review, 1974)
The authors have given anthropological measurements of a girl (5 years old) suffering from congenital short neck. The girl is morphologically underdeveloped (about 1 year retardation) and has strong compensative asymmetry of whole body. Her mother and brother (8 years old) are quite normal, but father has got distinct abnormalities in dental arch.